THE RIGHTS OF REFUGEES FROM UKRAINE IN THE REPUBLIC OF MOLDOVA - Anatoli BUZEV (Eastern European Journal of Regional Studies, 2023)
The refugee crisis in Ukraine generated by the intensity of military actions has highlighted the vulnerabilities faced by state institutions, affected by the large number of foreigners who have sought refuge on the territory of the Republic of Moldova. Both the Member States of the European Union and the Republic of Moldova have seen the security gaps that persist and must be removed. Change is a difficult and time-consuming process, and in the event of a massive influx of foreigners, it requires prompt and effective interventions. Actions in the management of the crisis situation put the authorities of the Republic of Moldova to the test. Thus, taking into account the effects of the refugee crisis in Ukraine, this paper consists in assessing national efforts in the context of the most efficient management of refugee flows seeking protection in the Republic of Moldova. This article aims to highlight the problem of the refugee crisis in Ukraine, the crisis conditioned by the Russo-Ukrainian war. The article also highlights the main issues regarding the granting by the Republic of Moldova of humanitarian aid to refugees from Ukraine, as well as respect for the rights of refugees in the Republic of Moldova.